Indonesian Education Trends Towards the Era of Society 5.0: Improving the Quality of Human Resources - Fitriana, Nurin; Hayuni Retno Widarti; Nur Indah Agustina (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
The Society 5.0 era is an era where technology has become part of every individual, which means technology plays an important role in solving the problems faced by society. Thanks to Society 5.0, intelligence that cares about human aspects will transform millions of data collected via the Internet in all areas of life, especially education. Therefore, the importance of human resource readiness in facing the Society 5.0 era. The research method uses a qualitative approach with qualitative descriptive analysis of literature reviews about improving the quality of human resources before the Society 5.0 era collected from several research journals. This article was written to improve the quality of human resources, especially in the field of education, in facing trends in educational development so that human resources are ready to welcome the new era, namely the era of Society 5.0. The research results show that the challenges of education in the era of Society 5.0 require thorough preparation with adequate human resources and utilizing technological advances in the education sector.